Comparison Effectiveness Learning Fiqh via Digital Media with Method Conventional for Al-Mutaqqin TPA Children - Umi Kasanah; Suhartono; Marlina (Tadrib: Jurnal Pendidikan Agama Islam, 2024)
Study This aim For evaluate use of digital media in learning at TPA. Interview results show that introduction learning with digital media, such as projector, accepted with good for children. The use of digital media creates a learning process more interesting and not boring, with enthusiasm more children high and engagement they in learning. Difference duration learning in a way overall between use of digital media and methods conventional No significant, though little use of digital media reduce time Because need install projector. Research also emphasizes importance time in learning. Material presented with fixed digital media based on the book he brought from boarding school, however obtain support from source from the internet or reference from the book of fatkhul ghorib. Therefore that , the use of digital media is not change the material taught, however makes it easier delivery material. Use of digital media in learning at TPA can be done help increase effectiveness learning, esp For overcome problem boredom student in method conventional. However, to each their own method learning own advantages and disadvantages, such as problem unfocus moment Study use method conventional. Teachers should too develop method learning that can be done make student involved or not bored, as well consider need specific from every student. Study This show that introduction modern technology in learning can increase effectiveness learning and creating a learning process become more interesting and easy understood by students. Therefore That's it, teachers should Keep going look for method For develop method appropriate learning with need students and can make optimal use of digital media.